Organic materials for all-optical signal processing and optical limiting - Perry, J; Hales, J; Chi, S; Cozzuol, M; Screen, T; Anderson, H; Matichak, J; Barlow, S; Marder, SR (2010)
Third-order nonlinearities and optical switching and limiting figures of merit are reported for several conjugated organic materials. Polymethines with large real to imaginary hyperpolarizability ratios and conjugated polymers with strong nonlinear absorption will be discussed. © 2010 Optical Society of America.